Exploiting the Potential of Artificial Intelligence in Decision Support Systems - Lal, Karu; Ballamudi, Venkata Koteswara Rao; Thaduri, Upendar Rao (ABC Journal of Advanced Research, 2018)
For several years now, the concept of AI being able to quickly and extensively replace expert workers at massive scales has been on the cusp of becoming a reality. Although AI has shown to be an effective tool for many activities, humans still have a significant advantage in many other areas. Companies are becoming more conscious of this fact. As a result, they are restructuring their business processes to provide their experts and customers with AI support in a more targeted manner. This study aims to present a high-quality review that covers unique, cutting-edge technologies and methodologies connected with the scientific design, development, and implementation of AI-DSS employing the most recent developments in AI and multi-criteria decision-making. The review will be presented in the form of a report. This article examines whether or not the growth of so-called artificial intelligence-driven decision support systems, also known as AI-DSS, threatens decision-making processes and, if so, how that threat manifests itself.